REFLECTION IN THE CASE STUDIES - Petr, MACH (Trends in education, 2013)
The Contribution focuses on the use of case studies in training of future teachers. The case studies are applied during the teaching process of subject didactics in study programs for future teachers. Students deal with all-embracing selected or assigned didactic tasks in model or simulated situations. Stage of videotape analysis, carried out the study, is important for the development of teacher competences. All-embracing analysis is not topic of contribution. It is mostly focused on a self-reflection and a self-perception of students. The research arrives to an intersting conclusion. Objective self-perception is a big problem for majority of the students.
Keywords: case study; teacher competences; self-reflection; pedagogic research